Switching to Bictegravir/Emtricitabine/Tenofovir Alafenamide (B/F/TAF) From Dolutegravir (DTG)+F/TAF or DTG+F/Tenofovir Disoproxil Fumarate (TDF) in the Presence of Pre-existing NRTI Resistance. (1st November 2020) - Acosta, Rima K.; Willkom, Madeleine; Andreatta, Kristen; Liu, Hui; Martin, Ross; Parvangada, Aiyappa; Martin, Hal; Collins, Sean; White, Kirsten L.
Abstract : Background: Study 4030 was a phase 3, randomized, double-blinded study of 565 HIV-1 RNA-suppressed participants switching to bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) or dolutegravir (DTG)+F/TAF. Nucleoside reverse transcriptase inhibitor (NRTI), non-NRTI, and protease inhibitor resistance (-R) was allowed, but integrase strand transfer inhibitor-R was excluded. Here, we describe the detailed resistance analysis. Methods: Historical plasma HIV-1 RNA genotypes and baseline proviral DNA genotypes were analyzed. Documented or investigator-suspected NRTI-R was grouped for stratification into 3 categories of level of resistance. Viral blips were assessed through week 48. Virologic failures had genotypic and phenotypic resistance analyses at week 48, confirmed failure, or last visit, if HIV-1 RNA did not resuppress to <50 copies/mL while on study drug. Results: In total, 83% (470/565) of participants had baseline genotypic data available with NRTI-R detected in 24% (138/565), including 5% (30/565) with K65R/E/N or ≥3 thymidine analog mutations and 19% (108/565) with other NRTI-R mutations. M184V/I was present in 14% (81/565). Pre-existing integrase strand transfer inhibitor-R mutations were found in 4% (20/565) of participants. Primary non-NRTI-R and protease inhibitor-R mutations were present in 21% (118/565) and 7% (38/565) of participants. High rates of viral suppression were maintained in all groups through week 48; blips were observed in only 15 participants (2.7%). Three participants met criteria for resistance analysis (all in DTG+F/TAF arm); none developed treatment-emergent resistance to study drugs. Conclusions: Participants with baseline NRTI resistance, much of which was previously undocumented, maintained suppression 48 weeks after switching to B/F/TAF or DTG+F/TAF triple therapy. Blips and virologic failure were uncommon using either regimen, with no treatment-emergent resistance.